Cultivating change: Exploring the link between certification, dietary quality and women's empowerment among coffee farmers in Rwanda - Sophia Bohn; Meike Wollni; Bruno Paz (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
Sustainability standards promise not only to promote environmentally friendly production, but also to improve farmers' livelihoods by linking them to high-value markets. While there has been extensive research on how sustainability standards affect farmers' incomes, much less attention has been paid to whether sustainability standards can help improve smallholders' diets. In addition, the link between the gender effects of sustainability standards and nutrition has remained largely unexplored. Using data from certified and non-certified coffee farmers in different districts of Rwanda, we assess the impact of certification on dietary quality. In addition, we examine women's empowerment as a potential pathway for the impact of sustainability standards on farmers' nutrition. We use inverse probability weighting regression adjustment and mediation analysis to estimate our results. We find positive associations between certification and dietary quality. Our results further suggest that women's empowerment is indeed a mediator of dietary quality, but that there may be other potential impact channels that need to be investigated. We conclude that efforts to improve women's empowerment within certification schemes can improve farmers' nutrition, but other complementary pathways need to be better understood.
Keywords: F63; I15; Q18; 330; Sustainability standards; Nutrition; Women’ s empowerment; Coffee; Rwanda